EDUCATION ATHLETES OF FAMILY OF LAKES REGION AND ITS INFLUENCE ON THE CHOICE AND SPORTING LIFE (Fiep Bulletin - online, 2017)
The family is the structural unit of society and its construction influence on the social development of the individual.Thus, it is believed in the importance of family education and its consequences in the social transformation of society. The socialindividual is configured through their social relations and their first social contact is with family, especially with their parents orguardians, so the transmission of knowledge, habits, ideas, attitudes, aptitudes and moral are initially built within family. Thesports habit can be developed by the individual or received in his personal experience, and is a playful way of caring for the healthfactor. It is believed that the practice of sports can be transmitted during social interaction within the family and this fact can be agreat generator of athletes committed to their sport and social training. This study sought to identify the influence of familyeducation in sports the hereditary line and its influence on social training of these athletes. He was interviewed a family of athletesJui-jitsu sport where the matriarch's regional successful athlete, state and national and children 8 years and 10 years whopractice the same sport mother and also have sporting success of the same scope. The objective was also to know how toinfluence and sports training of parents of each of the respondents and their influence on social formation thereof. It was foundthat the mother had parents that very little had access to sport and therefore did not influence the sporting life of the child and itsopposite, when this mother raised her children and influenced in their sports and that was important in the social formation ofthese children , according to these judged it to be.